THE EFFECT OF MANAGERIAL OWNERSHIP, INSTITUTIONAL OWNERSHIP, COMPANY GROWTH, LIQUIDITY, AND PROFITABILITY ON COMPANY VALUE - Eny Kusumawati; Adi Setiawan (Universitas Muhammadiyah Surakarta, 2019)
The purpose of this study is to study the effect of managerial ownership, institutional ownership, company growth, liquidity and profitability on value 65 manufacturing companies in the Indonesian Stock Exchange in the 2015-2017 period. The sampling technique used classic assumption tests and multiple linear regression analyzes with the help of SPSS 22 for windows. The results of the analysis show that: Managerial ownership and profitability affect the value of the company while institusional ownership, company growth, and liquidity do not affect the value of the company.